KOMUNIKASI PEMBANGUNAN MELALUI MEDIA SOSIAL UNTUK MEMBANGUN KEMANDIRIAN LOKAL - Ema, Ema (Jurnal Politikom Indonesiana, 2019)
This research was conducted to reveal the communication process towards local independence in the Karangpawitan Village through Social Media. The use of development communication strategies through social media through Karang Taruna empowerment can increase local income through local culinary tourism promotion activities. Karangpawitan which is commonly used for culinary tourism is also an icon for the city of Karawang, so this is what makes the reason why there is a need for a strategy to increase tourism there. To build local independence, a promotion through Social Media is needed. The method used is descriptive qualitative, which records symptoms that occur through observations and direct interviews with informants or through literature studies to compare existing data. The results show that communication strategies through promotion on social media are able to change the knowledge, attitudes, and behavior of audiences towards the income of local people. Through a strategy of changing knowledge to cultivate perceptions about culinary tourism, then being able to facilitate access to information about existing culinary and there is a change in attitude with the many netizens who come to try and take photos.